2020
DOI: 10.1371/journal.pone.0234355
|View full text |Cite
|
Sign up to set email alerts
|

Examination of different definitions of snacking frequency and associations with weight status among U.S. adults

Abstract: Snacks, while widely consumed in the United States (U.S.), do not have a standard definition, complicating research to understand associations, if any, with weight status. Therefore, the purpose of this study was to examine the association between snacking frequency and weight status using various snacking definitions that exist in the scientific literature among U.S. adults (NHANES 2013-2016; �20y n = 9,711). Four event-based snacking definitions were operationalized including participant-defined snacks, eati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 59 publications
2
30
0
Order By: Relevance
“…In our study, the simultaneous consumption of meals and snacks using a mobile phone or watching TV was not associated with anthropometric indices and abdominal obesity, which has been found in other studies (11).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In our study, the simultaneous consumption of meals and snacks using a mobile phone or watching TV was not associated with anthropometric indices and abdominal obesity, which has been found in other studies (11).…”
Section: Discussionsupporting
confidence: 79%
“…In this study, no signi cant relationship was found between the number of meals and snacks consumed with anthropometric indices, which was expected according to previous studies in this eld (11,12). In some studies, snack consumption, especially high-volume and high-calorie ingredients, has been cited as a reason for increased abdominal obesity (13), while in our study, no relationship was found between the number of snacks consumed and abdominal obesity.…”
Section: Discussionsupporting
confidence: 58%
“…Among the limitations of this study, the absence of a standardised classification of snacks stands out as a difficulty for comparing the findings of studies that evaluate meal habits (Cowan et al, 2020; Johnson & Anderson, 2010). In addition, the lack of a widely applied definition of snacks also undermines the possibility of understanding the role of snacks on health, since depending on the definition of snack adopted, it is possible that different effects are observed for a given outcome (Hess & Slavin, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Survey respondents selected the name of all eating occasions from a fixed list that was provided during the interview. According to the NHANES protocol, types of eating occasions consisted of breakfast, lunch, dinner, supper, brunch, snack, drink, and extended consumption (in addition to their Spanish equivalents: desayano , almuerzo , comida , merienda , cena , entre comida , botana , bocadillo , tentempie, bebida ) ( 38 , 39 ).…”
Section: Methodsmentioning
confidence: 99%